Individual and social determinants of obesity in strategic health messages: Interaction with political ideology. Issue 7 (2nd July 2016) - Young, Rachel; Hinnant, Amanda; Leshner, Glenn
ABSTRACT: Antiobesity health communication campaigns often target individual behavior, but these ads might inflate the role of individual responsibility at the expense of other health determinants. In a 2 × 2 full-factorial, randomized, online experiment, 162 American adults viewed antiobesity advertisements that varied in emphasizing social or individual causation for obesity through text and images. Locus for attribution of responsibility for obesity causes and solutions was measured, as was how these responses were moderated by political ideology. Participants who viewed text emphasizing individual responsibility were less likely to agree that genetic factors caused obesity. Conservative participants who viewed images of overweight individuals were less likely than liberal participants to agree that social factors were responsible for causing obesity. In addition, among conservative participants who viewed images of fast food versus images of overweight individuals, agreement that the food industry bore some responsibility mediated support for policy solutions to obesity. These findings, among others, demonstrate that awareness of multilevel determinants of health outcomes can be a precursor of support for policy solutions to obesity among those not politically inclined to support antiobesity policy. In addition, stigmatizing images of overweight individuals in antiobesity campaigns might overemphasize the role of individual behavior in obesity at the expense of other factors.